IMMUNE MECHANISMS UNDERLYING LONG-TERM COVID: AN UPDATE FROM THE COLLEGIUM INTERNATIONALE ALLERGOLOGICUM 2024 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can lead to a prolonged multisystem disorder called long COVID, which may affect up to 10% of people following coronavirus disease 2019 (COVID-19). It is currently unclear why some people do not fully recover from SARS-CoV-2 infection. In this review, we examine the immunological mechanisms that may underlie the pathophysiology of long COVID. These mechanisms include an inappropriate immune response to acute SARS-CoV-2 infection, immune cell exhaustion, metabolic reprogramming of immune cells, a persistent SARS-CoV-2 reservoir, reactivation of other viruses, inflammatory responses affecting the central nervous system, autoimmunity, microbiome dysbiosis, and dietary factors. Key messages: Unfortunately, currently available diagnostic and treatment options for long COVID are inadequate, and additional clinical trials that match experimental interventions to underlying immunological mechanisms are needed.